4CPS-185 Copd: monitoring the therapeutical adherence and the appropriate use of drugs classified in atc r03. (2nd March 2018) - Uomo, I; Pastorello, M
Abstract : Background: COPD is a chronic inflammatory pathology that involves a massive consumption of resources for the National Health System (NHS). Therapeutical adherence and appropriateness is very low, which showed both in the national reports of drug utilisation in local data. All the treatments are long-term therapies and were reimbursed by the NHS. The pharmacists have to monitor the prescriptions of the territory (1, 300, 000 inhabitants). Purpose: Our analysis aims to evaluate the use of drugs in patients with COPD over the period 2014 to 2016. Particularly, switches between therapies, the commercialisation of new drugs, volumes, adherence (consumption of more than 80% of the annual prescribed medications) and the impact of new therapies on the pharmaceutical expenditure. Material and methods: Data were collected by the pharmaceutical flow of the reimbursed therapy, through extraction from an Access database. The pharmacists analysed volumes, percentage of the drug utilisation for each class, and creating a benchmark of 3 years of expenditure and consumption. We also calculated adherence to the treatment. Results: During the observed period the data almost remains the same: population over 45 years treated totalled 5 90 000 patients/year with a prevalence of COPD of 21%. The most prescribed class is the ICS/LABA (R03AK). The adherence for ICS/LABAs therapies in the population is very low, approximately 38% of the population considered. In 2016, there was a reduction in the use of ICS/LABAs twice-daily, with an increase in once-daily therapies, i.e. fluticason furoate/vilanterol (reimbursed since 2015). These switches mean an important reduction in pharmaceutical spending by €208, 000 (2016 vs 2015), despite the volume of prescriptions being increased by 8000 packages per year. An over-prescription of ICS in monotherapy (off-label in the COPD) emerged. Conclusion: Adherence is very low, but our results are better than the Italian OSMED data of recent years (not more than 29% in the period 2014 to 2015) and justifies the work done by the pharmacists of the Pharmaceutical Department, training and constantly informing the clinicians. Achieving significant savings and increasing the number of patients treated in terms of packs/year support the use of new single-administration association therapies. References and/or Acknowledgements: L'uso dei farmaci in Italia-Rapporto OsMed 2015. The Medicines Utilisation Monitoring Centre. National Report on Medicines use in Italy. Year 2015. Rome: Italian Medicines Agency 2016. No conflict of interest